Proton Grid Therapy: A Proof-of-Concept Study. (December 2017) - Henry, Thomas; Ureba, Ana; Valdman, Alexander; Siegbahn, Albert
In this work, we studied the possibility of merging proton therapy with grid therapy. We hypothesized that patients with larger targets containing solid tumor growth could benefit from being treated with this method, proton grid therapy. We performed treatment planning for 2 patients with abdominal cancer with the suggested proton grid therapy technique. The proton beam arrays were cross-fired over the target volume. Circular or rectangular beam element shapes (building up the beam grids) were evaluated in the planning. An optimization was performed to calculate the fluence from each beam grid element. The optimization objectives were set to create a homogeneous dose inside the target volume with the constraint of maintaining the grid structure of the dose distribution in the surrounding tissue. The proton beam elements constituting the grid remained narrow and parallel down to large depths in the tissue. The calculation results showed that it is possible to produce target doses ranging between 100% and 130% of the prescribed dose by cross-firing beam grids, incident from 4 directions. A sensitivity test showed that a small rotation or translation of one of the used grids, due to setup errors, had only a limited influence on the dose distribution produced in the target, if 4 beam arrays were used for the irradiation. Proton grid therapy is technically feasible at proton therapy centers equipped with spot scanning systems using existing tools. By cross-firing the proton beam grids, a low tissue dose in between the paths of the elemental beams can be maintained down to the vicinity of a deep-seated target. With proton grid therapy, it is possible to produce a dose distribution inside the target volume of similar uniformity as can be created with current clinical methods.